Etnični konflikti in varnost Makedonije - Tatalović, Siniša (Teorija in praksa, 1999)
Research on ethnic conflicts and their solving is extremely important since everybody belongs to some ethnic community and common relations are far too important to be left to ethnical partiality. This is why analyses on the ways of solving ethnic conflicts are fundamental responsibility for researchers dealing with the questions of national and international security in a broader sense and ethnic conflicts in a narrower sense. The article analyses ethnic conflicts and the ways of solving them in the case of Macedonia, which is traditionally burdened with ethnic conflicts of various kinds and intensity. After the gaining independence in 1991, Macedonia started a hard way of preserving independence and territorial integrity. Entirely disarmed, with great internal problems and conflicts and disinclined environment of neighbour countries, Macedonia searched for the ways of its own security. Because of the modest defensive and security forces, Macedonia relied on foreign forces, especially on USA, which in Macedonia saw the support for its politics on the Balkans. In the process of state building and integration into international organisations Macedonia achieved discernible success, although it still faces numerous problems, conditioned by internal, especiallyethnic conflicts and unstable environment, e.g. Kosovo. Visible results were achieved at defining ethnic minorities rights, particularly for Albanians. However, its chances for successful defence in the case of clash ofarms, are without foreign help very small. According to a very unfavourable scenario, Macedonia would be forced to solve conflicts with internal para-military forces as well as with the troops of some neighbour countries.
Keywords: Makedonija; Republic of Macedonia; politične razmere; etnični konflikti; Balkan; Balkans; narodne manjšine; mednacionalni odnosi; nacionalna varnost